Optimization of Pharmaceutical R&D Programs and Portfolios : Design and Investment Strategy - Antonijevic, Zoran (Springer International Publishing : Imprint: Springer, 2015)
Very little has been published on optimization of pharmaceutical portfolios. Moreover, most of the published literature comes from the commercial perspective, where probability of technical success (PoS) is treated as fixed, and not as a consequence of development strategy or design. In this book there is a strong focus on the impact of study design on PoS, and ultimately a portfolio's value. Design options that are discussed are dose-selection strategies, adaptive design, and enrichment. Some development strategies that are examined are indication sequencing, optimal number of programs, and optimal decision criteria.     This book includes chapters written by authors with very broad backgrounds including financial, clinical, statistical, decision sciences, commercial, and regulatory. Many authors have long held executive positions and have been involved with decision making at a product or at a portfolio level. As such, it is expected that this book will attract a very broad audience, including decision makers in pharmaceutical R&D, commercial, and financial departments. The intended audience also includes portfolio planners and managers, statisticians, decision scientists, and clinicians. Early chapters describe approaches to portfolio optimization from big pharma, and venture capital standpoints, focusing on finances and processes. Later chapters present selected statistical and decision analysis methods for optimizing drug development programs and portfolios. Some methodological chapters are technical; however, with a few exceptions they require a basic knowledge of statistics by a reader. .